(untitled) (Memorias Sifored - Encuentros Educación UAN, 2023)
Access to higher education in Colombia is undoubtedly a challenge, however, this is limited by several factors that unfortunately have worsened over time. These obstacles especially affect the underprivileged classes in both public and private universities. To address this need, different models of financial aid are created, such as the Colombian Institute of Educational Credit and Technical Studies Abroad (ICETEX), an entity that aims to provide student loans or financing to allow more people in vulnerable conditions to access higher education, which apparently is not a reality and these credits continue to contribute to social inequality. With this research we intend from a literature review to understand the influence that a credit of this type has on access to higher education in the city of Bogota, addressing from the concept of education as a constitutional right; the social origin of ICETEX, quality, coverage and access to education until reaching the conclusion with the term educational apartheid (Garcia, 2013. p.43) that refers to social segregation in the city of Bogota.